PENGARUH LITERASI DENGAN MODEL INQUIRI TERBIMBING DALAM MELATIHKAN KETERAMPILAN PROSES SAINS SISWA MI NURUL HUDA MOJOKERTO - Novaria Lailatul Jannah (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
This study aims to study the effect of literacy with a guided inquiry model on the Science Process Skills of MI Nurul Huda Students, Mojokerto Regency. This research uses quantitative research. The type of approach is descriptive quantitative research, namely research to provide an overview of the symptoms, phenomena, or facts studied by describing the values of independent variables, without intending to connect or compare. From the results of the study, the influence of literacy and guided inquiry on the development of students' science process skills has a value of 78.1%, thus the variable indicates a sufficient category. This means that literacy on the development of science process skills is quite influential for students at MI Nurul Huda